Antibacterial activities of titanium dioxide (TiO2) nanotube with planar titanium silver (TiAg) to prevent orthopedic implant infection - Hongli Zhang; Zhihui Jin (Journal of Orthopaedic Surgery and Research)
Abstract Background Orthopedic implant infection has become a common catastrophic complication after various orthopedic implants, which can lead to prolonged use of antibiotics and even surgical failure. The quality of care (QoC) of orthopedic implant infection is very important. Methods Titanium dioxide (TiO2) nanotube array with planar TiAg was prepared, and their antibacterial rates were tested. 400 patients hospitalized in the Department of Orthopedics of Wuhan Fourth Hospital from May 2019 to May 2020 were selected as controls (before QoC evaluation system of orthopedics), and 400 patients hospitalized from June 2020 to June 2021 were selected as observation group (after QoC evaluation system of orthopedics). Results Regardless of Staphylococcus aureus or Escherichia coli, the antibacterial rate of TiO2 nanotube array with planar TiAg was clearly higher than that of pure iron film on the 10th and 20th days (P < 0.05). The accuracy of hospitalization assessment, disease assessment, adverse event intervention, nursing record filing and nursing satisfaction in observation group were higher as against controls (P < 0.05). Conclusion The TiO2 nanotube array with planar TiAg has good antibacterial property, which can effectively prevent orthopedic implant infection. The construction of QoC evaluation system for orthopedic specialists can effectively improve the QoC of orthopedic specialists.